Hubungan antara Obesitas, Pola Makan, dan Nyeri Saat Buang Air Besar pada Anak dengan Konstipasi Fungsional: Tinjauan Literatur: Tinjauan Pustaka - Nuridah, Ayu Lilyana; Putri, Awalya Rahma; Anggraeni, Yunita Dewi; Shodikin, Muhammad Ali (Cermin Dunia Kedokteran, 2026)
Background: Functional constipation is defined as delayed or difficult bowel movements lasting ≥2 weeks that cause the patient distress. This study aims to examine the relationship between obesity, dietary patterns, and defecation pain with the incidence of functional constipation in children. Methods: A literature review was conducted using predefined keywords from data sources Google Scholar, PubMed, and ScienceDirect. Inclusion criteria included open-access articles published between 2014 and 2024. A total of 9 articles that met the criteria were further analyzed. Results: Functional constipation is associated with several risk factors, including obesity, unhealthy dietary patterns, and defecation pain. Some studies showed a positive correlation between obesity and functional constipation, although the results varied and were not always statistically significant. Low-fiber, high-fat diets have been reported to impair intestinal motility. Pain during defecation may reinforce the behavior of stool withholding, which ultimately worsens constipation symptoms. Conclusion: This review highlights the importance of factors such as obesity, dietary habits, and defecation pain in preventing and managing functional constipation in children.